Health situation of migrant and minority nurses: A systematic review. - Benjamin Schilgen; Albert Nienhaus; Oriana Handtke; Holger Schulz; Mike Mösko (PLoS ONE)
Introduction Globally, life expectancy together with multimorbidity and chronic diseases are increasing. This leads to a growing demand for care and hence for healthcare personnel and nurses. To meet this demand, healthcare workers from abroad are increasingly hired. The nurses' workplace in general is characterized by physically and psychologically demanding tasks, while that of migrant and minority nurses is additionally characterized by discriminatory practices. The present knowledge about the health of migrant and minority nurses and the terminology in this context are diverse. Thus, the purpose of this review is to systematically identify and synthesize international publications that explicitly focus on migrant nurses' health. Materials and methods A systematic review of relevant studies was undertaken using the databases Medline, PsycINFO, CINAHL and Web of Science. The screening process was conducted in several phases. This review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines while the methodological quality assessment of the included papers was performed with the Mixed Method Appraisal Tool (MMAT). Results Out of 11,599 citations initially obtained, 14 empirical studies were included in the final synthesis. The methodological quality of the empirical studies and reviews was diverse. The majority of the studies were conducted in the US and the nurses under study migrated from countries like the Philippines, India, Europe, and Africa. Among migrant nurses of different origins, there are differences in their physiological responses to stress. Migrant nurses and native nurses differ in reporting work-related injuries. Discussion Migrant and minority nurses are at high risk of work-related injuries and discrimination than native or majority nurses. However, mixed results were obtained, namely that the reported health of migrant nurses either improves over time or it decreases. This review revealed that discrimination is the leading cause of impaired health amongst migrant and minority nurses.